Dielectric properties of Sr0.75Ba0.25Nb 2O6 thin films: Bias field, frequency and temperature dependence - Mendes, R. G.; Santos, I. A.; Araújo, E. B. [UNESP]; Eiras, J. A. (Taylor & Francis Ltd, 2002)
Ferroelectric strontium barium niobate solid solutions had received great attention due to their excellent pyroelectric, electrooptic and photorefractive properties. Furthermore, they usually also present very interesting phase transition characteristics. In this work, polycrystalline single phase Sr 0.75 Ba 0.25 Nb 2 O 6 thin films were prepared by a hybrid chemical method and deposited on Pt/Ti/SiO 2 /Si substrates. The temperature dependence of dielectric constant was measured at different frequencies and bias field levels. The presence of two dielectric dispersion regions with relaxor characteristics was observed at distinct temperature ranges, corresponding to the ferro-paraelectric and to a structural phase transition at low temperatures, respectively. A specific dielectric dispersion region, associated with an incommensurate superstructure frequently observed in bulk samples, was not observed in this films probably due to their small grain sizes. © 2002 Taylor & Francis.
Keywords: Ferroelectric relaxors; Niobates; Phase transitions; Thin films; Dielectric properties; Electrooptical effects; Ferroelectric materials; Permittivity; Pyroelectricity; Structural phase transition; Superstructures